Giornata di Studio per Giovani Ricercatori su Innovazione Tecnico Scientifica in Italia nei Settori dell'Energia Elettrica e ICT - Fantacci, Romano (Proceedings e report, 2009)
This book comprises the contributions presented at the Study Day addressing technical and scientific innovation in Italy in the sectors of electricity and telecommunications, organised in the Faculty of Engineering of Florence University by AICT (Associazione per la Tecnologia dell'Informazione e delle Comunicazioni) and AEE (Associazione Energia Elettrica, of the AEIT Federation) in the framework of the celebrations marking the bicentenary of the birth of Antonio Meucci. The first section presents three addresses by guest speakers dealing with the past, present and future of telecommunications, while the second section consists of nine articles selected on open-call basis representing original contributions from young researchers in the sectors of electricity and telecommunications.